Acute Pelvic and Hip Apophyseal Avulsion Fractures in Adolescents: A Summary of 719 Cases. Issue 4 (23rd April 2023) - Ferraro, Samantha L.; Batty, Miles; Heyworth, Benton E.; Cook, Danielle L.; Miller, Patricia E.; Novais, Eduardo N.
Abstract : Background: Apophyseal avulsion fractures of the pelvis and hip are common injuries in adolescent athletes. However, high volume comparative studies elucidating the spectrum of injuries are largely absent from the literature. The current study provides a comprehensive analysis of demographic, anatomic, pathophysiological, clinical, and athletic-related variables associated with such injuries in an extensive population of affected adolescents. Methods: A retrospective review was performed of records of patients presenting to a single tertiary care pediatric hospital between January 1, 2005, and July 31, 2020, collecting variables including patient sex, age, body mass index, fracture location, injury mechanism, sport at the time of injury, and duration of prodromal symptoms. Results: Seven hundred nineteen fractures were identified in 709 patients. The average patient age was 14.6, and 78% of the fractures occurred in male patients. The anterior inferior iliac spine (33.4%), anterior superior iliac spine (30.5%), and ischial tuberosity (19.4%) were the most common fracture sites. The most common injury mechanisms were running (27.8%), kicking (26.7%), and falls (8.8%). The most common sports at the time of injury were soccer (38.1%), football (11.2%), and baseball (10.5%). Fracture site was significantly associated with patient sex, age, body mass index, laterality, mechanism, sport, time from injury, and presence of prodromal symptoms. The annual volume of pelvic avulsion fractures treated at the institution increased significantly from n=17 in 2005 to n=75 in 2019. Conclusions: Adolescent pelvic and hip avulsion fractures occur during a narrow window of age and skeletal maturation and are frequently sustained during sporting activities. Each fracture location is associated with certain demographic, mechanistic, and patient-specific characteristics. The associations between fracture site and patient-specific or injury-specific variables offer insights into the pathophysiology and possible underlying biomechanical risk factors that contribute to these injuries. Level of Evidence: This is a level III retrospective study.